The anti‐cancer effect of chitosan/resveratrol polymeric nanocomplex against triple‐negative breast cancer; an in vitro assessment - Azam Bozorgi; Zahra Haghighi; Mohammad Rasool Khazaei; Maryam Bozorgi; Mozafar Khazaei (IET Nanobiotechnology)
Abstract Herein, the authors synthesised chitosan nanoparticles (Cs NPs) as a resveratrol (RSV) carrier and evaluated their efficacy in stimulating apoptosis in MDA‐MB 231 cells. Blank (Cs NPs) and RSV‐ Cs NPs (RSV‐Cs NPs) were synthesised via ionic gelation and characterised by using fourier‐transform infrared spectroscopy (FTIR), Scanning electron microscope, dynamic light scattering/Zeta potential and RSV release. MDA‐MB 231 cells were treated with RSV, Cs NPs and RSV‐Cs NPs (24, 48, and 72 h), followed by the 3‐[4,5‐dimethylthiazol‐2‐yl]‐2,5‐diphenyltetrazolium bromide assay. Cell toxicity was evaluated using lactate dehydrogenase assay, and real‐time polymerase chain reaction was performed to explore apoptosis induction. FTIR spectra confirmed the NPs via the formation of cross‐linking bonds. Cs and RSV‐Cs NPs sizes were about 75 and 198 nm with 14 and 24 mV zeta potentials. The RSV entrapment efficiency was 52.34 ± 0.16%, with an early rapid release followed by a sustained manner. Cs and RSV‐Cs NPs inhibited cell proliferation at lower concentrations and IC50 values. RSV‐Cs NPs had the most cytotoxic effect and stimulated intrinsic apoptotic pathway, indicated by increased Bcl‐2‐associated x (BAX), BAX/Bcl‐2 ratio, P53 expressions, reduced Bcl‐2 and upregulated caspases 3, 8 and 9. RSV‐Cs NPs have a great potential to suppress invasive breast cancer cell proliferation by targeting mitochondrial metabolism and inducing the intrinsic apoptotic pathway.